Achieving beneficial outcomes for children with life-limiting and life-threatening conditions receiving palliative care and their families: A realist review. (March 2020) - Mitchell, Sarah; Bennett, Karina; Morris, Andrew; Slowther, Anne-Marie; Coad, Jane; Dale, Jeremy
Background: Palliative care for children and young people is a growing global health concern with significant resource implications. Improved understanding of how palliative care provides benefits is necessary as the number of children with life-limiting and life-threatening conditions rises. Aim: The aim is to investigate beneficial outcomes in palliative care from the perspective of children and families and the contexts and hidden mechanisms through which these outcomes can be achieved. Design: This is a systematic realist review following the RAMESES standards. A protocol has been published in PROSPERO (registration no: CRD42018090646). Data sources: An iterative literature search was conducted over 2 years (2015–2017). Empirical research and systematic reviews about the experiences of children and families in relation to palliative care were included. Results: Sixty papers were included. Narrative synthesis and realist analysis led to the proposal of context–mechanism–outcome configurations in four conceptual areas: (1) family adaptation, (2) the child's situation, (3) relationships with healthcare professionals and (4) access to palliative care services. The presence of two interdependent contexts, the 'expert' child and family and established relationships with healthcare professionals, triggers mechanisms, including advocacy and affirmation in decision-making, which lead to important outcomes including an ability to place the emphasis of care on lessening suffering. Important child and family outcomes underpin the delivery of palliative care. Conclusion: Palliative care is a complex, multifactorial intervention. This review provides in-depth understanding into important contexts in which child and family outcomes can be achieved so that they benefit from palliative care and should inform future service development and practice.